2017
DOI: 10.1001/jamafacial.2016.2206
|View full text |Cite
|
Sign up to set email alerts
|

Association of Face-lift Surgery With Social Perception, Age, Attractiveness, Health, and Success

Abstract: IMPORTANCE Evidence quantifying the influence of face-lift surgery on societal perceptions is lacking.OBJECTIVE To measure the association of face-lift surgery with observer-graded perceived age, attractiveness, success, and overall health. DESIGN, SETTING, AND PARTICIPANTSIn a web-based survey, 526 casual observers naive to the purpose of the study viewed independent images of 13 unique female patient faces before or after face-lift surgery from January 1, 2016, through June 30, 2016. The Delphi method was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Previous studies have shown the following points: 1. The face is the central contributor to physical attractiveness; 3 2. Each facial component may be related to facial attractiveness; 8 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown the following points: 1. The face is the central contributor to physical attractiveness; 3 2. Each facial component may be related to facial attractiveness; 8 3.…”
Section: Discussionmentioning
confidence: 99%
“…An individual with a beautiful face may appear younger, healthier, more attractive and successful. 3 Discrimination is relatively frequent among people who are facially unattractive. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The multivariate mixed-effects regression model is one that has been used previously to study how face-lift surgery alters societal perceptions. 31 It was discovered that adding upper facial rejuvenation to the face-lift procedure yields a larger clinical effect size in the age domain (patients appeared more youthful when undergoing face-lift and upper facial procedures as compared with face-lift alone). These results are relevant even in the setting of an essential difference in the study designs; the face-lift study was conducted using only photographs of the best surgical results, whereas the present study contains photographs with a range of postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We have addressed the social aspects of face perception (e.g., attractiveness and emotional expressions) as they have consistently been recognized as fundamental to human social interaction [12,13,14,15,17,18,19,20,21,22,23,38,39,40,41,42,43,54,55,56,57]. However, research on the OGS population should be expanded to additional facial−perception−associated areas of interest, such as neuropsychological mechanisms, through a multidisciplinary research collaboration with groundbreaking engineering technologies (e.g., brain scanning, direct stimulation of the brain, visual adaptation, and single−cell recording) [58,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few OGS studies have adopted the FACE-Q tool [10,11]. In this setting, the impact of different surgical interventions, including OGS procedures, on facial aesthetic and social perceptions, has been demonstrated using the panel assessment tool, a metric that is centered on clinician-reported outcome (ClinRO, professionals using medical or dental judgments) and observer-reported outcome (ObsRO, judgments from laypersons with no formal training) principles [12,13,14,15,16,17,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%